Theoretical aspects of improving the methodological work of a higher education institution department - Burbiga, V. A. (Problems of Engineer-Pedagogical Education, 2018)
The article is devoted to an important educational problem which is theoretical substantiation of the features of improving the methodological work of a higher education institution department. Methodological work is a purposeful activity of any higher education institution department which consists in providing psychological, pedagogical and methodological training of teachers with the aim of increasing the efficiency of their educational activities. It contributes to the personal development of the teacher, his/her pedagogical skills in teaching and carrying out extracurricular upbringing activity. The article states that the implementation of innovative forms of methodological work at a higher education institution department promotes the involvement of teachers in active cooperation, acquaintance with the latest pedagogical technologies, development of a positive attitude to modern methods of teaching and an interest in using them. Special attention is drawn to the reasonability of organizing creative educational fairs, festivals of pedagogical ideas and findings, methodological vernissages, panoramas of creative findings, pedagogical consiliae, methodological auctions, problem-solving seminars, creative scientific discussions, pedagogical tournaments that enhance scientific orientation of methodological work, encourage teachers to work more actively, develop their general erudition. The article proves that the creation of a departmental Electronic Methodological Cabinet will contribute to the development of a scientific and methodological work system, encourage the introduction of innovative teaching and upbringing technologies, boost teachers‟ creativity, widen their scientific outlook and develop pedagogical skills.